The Concept of Islamic Guidance and Counseling In Surah At-Tahrim Verse 6 on the Development of Adolescent Morals - Fitti Nurhaliza; Diana; Uci Purnama; Inda Royani; Wimra Sahara; Siti Rahma Harahap (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze the concept of Islamic guidance and counseling contained in Surah At-Tahrim verse 6 and its relevance to the moral development of adolescents. This study uses a library research method by collecting data from various literary sources such as the Qur'an, tafsir books, books, and scientific journals related to Islamic guidance and counseling and the moral development of adolescents. The data collection technique is carried out through documentation, while the data analysis uses content analysis techniques. The results of the study indicate that Surah At-Tahrim verse 6 contains the concept of Islamic guidance and counseling which includes the responsibility of education, direction and advice, supervision, and role models. These concepts have an important role in the moral development of adolescents because they can help shape the character of faith, piety, and noble character. In addition, the verse emphasizes that the family, especially parents, have the primary responsibility in guiding and protecting adolescents from various behaviors that deviate from Islamic teachings. Thus, the concept of Islamic guidance and counseling in Surah At-Tahrim verse 6 can be used as a basis for efforts to develop adolescent morals in the family and educational environment.